Clinical efficacy of T-cell therapy after short-term BRAF-inhibitor priming in patients with checkpoint inhibitor-resistant metastatic melanoma. Issue 7 (1st July 2021) - Borch, Troels Holz; Harbst, Katja; Rana, Aynal Haque; Andersen, Rikke; Martinenaite, Evelina; Kongsted, Per; Pedersen, Magnus; Nielsen, Morten; Kjeldsen, Julie Westerlin; Kverneland, Anders Handrup; Lauss, Martin; Hölmich, Lisbet Rosenkrantz; et al.
Abstract : Purpose: Despite impressive response rates following adoptive transfer of autologous tumor-infiltrating lymphocytes (TILs) in patients with metastatic melanoma, improvement is needed to increase the efficacy and broaden the applicability of this treatment. We evaluated the use of vemurafenib, a small-molecule BRAF inhibitor with immunomodulatory properties, as priming before TIL harvest and adoptive T cell therapy in a phase I/II clinical trial. Methods: 12 patients were treated with vemurafenib for 7 days before tumor excision and during the following weeks until TIL infusion. TILs were grown from tumor fragments, expanded in vitro and reinfused to the patient preceded by a lymphodepleting chemotherapy regimen and followed by interleukin-2 infusion. Extensive immune monitoring, tumor profiling and T cell receptor sequencing were performed. Results: No unexpected toxicity was observed, and treatment was well tolerated. Of 12 patients, 1 achieved a complete response, 8 achieved partial response and 3 achieved stable disease. A PR and the CR are ongoing for 23 and 43 months, respectively. In vitro anti-tumor reactivity was found in TILs from 10 patients, including all patients achieving objective response. Serum and tumor biomarker analyses indicate that baseline cytokine levels and the number of T cell clones may predict response to TIL therapy. Further, TCR sequencing suggested skewing of TCR repertoire during in vitro expansion, promoting certain low frequency clonotypes. Conclusions: Priming with vemurafenib before infusion of TILs was safe and feasible, and induced objective clinical responses in this cohort of patients with checkpoint inhibitor-resistant metastatic melanoma. In this trial, vemurafenib treatment seemed to decrease attrition and could be considered to bridge the waiting time while TILs are prepared.